The blockade of the renin-angiotensin system reverses tacrolimus related cardiovascular toxicity at the histopathological level - TUĞLULAR, ZÜBEYDE SERHAN (J R A A S LTD, 2007)
Introduction. In this study, we investigate the toxic effects of tacrolimus (FK506) on the cardiovascular system at the histopathological level in a rat model and whether these effects can be reversed by the blockade of the renin-angiotensin system (RAS) by either an angiotensin-converting enzyme inhibitor (ACE-inhibitors) or an angiotensin receptor antagonist (ARB). Methods and results. Thirty-one Wistar rats were divided into four groups. FK506 group was treated with FK506 intraperitoneally (i.p.), FK506+ACE-inhibitors and FK506+ARB groups were treated with either quinapril or valsartan orally in addition to FK506. Control group was treated with saline i.p. Histological and immunohistochemical staining of cardiovascular tissue in the FK506 group showed increased vacuolar degeneration (11.2 vs. 5.8, p=0.008), arterial hyalinosis (10.7 vs. 6.3, p=0.036), transforming growth factor-beta (TGF-P) (12.2 vs. 4.8, p=0.001) and vascular endothelial growth factor expression (VEGF) (10.7 vs. 6.3, p=0.036), elastic van Gieson (11.5 vs. 5.5, p=0.004), and periodic acid Schiff stain scores (12.5 vs. 4.5, p < 0.001) compared to the control group. Immunoihistochemical scores showed that expression of TGF-P is up-regulated, and bone morphogenic protein (BMP-7) is down-regulated with FK506 toxicity.Adding RAS blockade with either an ACE-inhibitor or an ARB could reverse FK506 induced changes. Both FK506+ACE-inhibitors and FK506+ARB groups demonstrated decrease in arterial hyalinosis (22.1 vs. 14.4 (FK5o6+ACE-inhibitor) and 13.6 (FK506+ARB), p=0.09) and vacuolar degeneration (23.1 vs. 16.1 (FK506+ACEinhibitor) and 12.4 (FK506+ARB), p=0.006) scores compared to the FK506 group. Conclusion. Blockade of RAS could reverse the histopathological signs of FK506 induced cardiac toxicity in a rat model.
Keywords: tacrolimus; cardiac toxicity; renin-angiotensin system; GROWTH-FACTOR-BETA; MESANGIAL CELLS; TGF-BETA; TRANSPLANT RECIPIENT; FK506 NEPHROTOXICITY; DIABETES-MELLITUS; CYCLOSPORINE-A; RATS; EXPRESSION; FIBROSIS